Marketing Philosophy of Indian Banking Industry : New Trends - Rawat, G. S (Journal of Commerce and Trade, 2008)
The choice-empowered customer is now commanding position to the throne, to borrow an expression from military literature, dictating terms and proclaiming kingship. There is no any other way except for bankers to wake up to this emerging reality and realize that, to be competitive. One must necessarily have to be customer focused. For this reason, banker’s missions are no longer product, profit or even market oriented, but only focused on customer’s supremacy. Technological competence can be a vital support, but marketing knowledge holds the key. In most of the conventional banks the basic strength is the foundations of larger customers for decades that are loyal. The scenario is not going to be the same for long. The entry of foreign banks and emergence of new private banks have brought about certain market scales, which were not present before. Many new novelties like bank expertise, new initiatives, and functional pattern have emerged. There are quite a lot of things to follow in the system and styles of foreign banks. The question therefore boils down to the need to be efficient and quick to understand the changing customer profile and customer requirements. Customer will dominate the market. Bank with full capabilities for developing innovative products structuring and down selling assets, offering floating rates for both loan and deposits has also operating in global foreign exchange markets will be winners. For this propose credit management, product development market research and treasury operations are the thrust areas which could require focused attention.